Self-triggered-organized Mecanum-wheeled robots consensus system using model predictive based protocol - Xiao, Hanzhen; Yu, Dengxiu; Chen, C.L. Philip (Information sciences, 2022)
In this work, for smoothly achieving the leader–follower consensus formation of multiply omni-mecanum-wheeled robots (OMWRs) with switching desired relative configurations, a self-triggered-organized formation (STOF) system based on distributed model predictive control (DMPC) consensus protocol is proposed. In the STOF system, OMWRs’ communication topologies can be timely updated to fit their current formation states through designing the STO condition and updating rules. Through using the self-smoothing transformation mechanism, the jerking of states and velocities in the STOF system can be avoided. After constructing the consensus tracking error system based on the dynamic model of OMWRs, a distributed model predictive control (DMPC) based consensus protocol is utilized to get the optimal input signals for each robot, and the constraints can be synchronically handled. Finally, the results of simulations verify the effectiveness of the developed control scheme.